The Effectiveness and Recommendation of Motor Imagery Techniques for Rehabilitation after Anterior Cruciate Ligament Reconstruction: A Systematic Review. - Pastora-Bernal, José Manuel; Estebanez Pérez, María José; Lucena-Antón, David; García López, Francisco José; Bort Carballo, Antonio; Martín-Valero, Rocío (MDPI, 2021)
Motor imagery (MI) reported positive effects in some musculoskeletal rehabilitation processes. The main objective of this study was to analyze the effectiveness of MI interventions after anterior cruciate ligament (ACL) reconstruction. A systematic review was conducted from November 2018 to December 2019 in PubMed, Scopus, Web of Science, The Cochrane Library, and Physiotherapy Evidence Database (PEDro). The methodological quality, degree of recommendation, and levels of evidence were analyzed. A total of six studies were included. Selected studies showed unequal results (positive and negative) regarding pain, anxiety, fear of re-injury, function, and activities of daily living. Regarding the range of motion, anthropometric measurements, and quality of life, the results were not conclusive. Muscle activation, strength, knee laxity, time to remove external support, and neurobiological factors showed some favorable results. Nevertheless, the results were based on a limited number of studies, small sample sizes, and a moderate-weak degree of recommendation. In conclusion, our review showed a broader view of the current evidence, including a qualitative assessment to implement MI after ACL surgery. There was no clear evidence that MI added to physiotherapy was an effective intervention after ACL surgery, although some studies showed positive results in clinical outcomes. More adequately-powered long-term randomized controlled trials are necessary. Keywords: anterior cruciate ligament; motor imagery techniques; rehabilitation; physiotherapy
Keywords: Fisioterapia; Ligamentos cruzados anteriores; Rehabilitación - Innovaciones tecnológicas; Anterior cruciate ligament; Motor imagery techniques; Physiotherapy; Rehabilitation